A Study of Driving Cycle for Electric Special-purpose Vehicle in Beijing. (May 2017) - Zhang, Fei; Guo, Fen; Huang, Hong
Abstract: In this paper, the driving cycle of electric special-purpose vehicle in Beijing is investigated. Firstly a reasonable experimental scheme is made, in which several electric van trucks are selected to represent the special-purpose vehicle. A new type of data collection transmission and management system based on GPRS communication is used. Then the obtained data is preprocessed and divided into microtrips, and many characteristic parameters are selected. Finally, a representative driving cycle of electric van trucks for the typical roads in Beijing is worked out by principal component analysis and k-means clustering method. Besides, compared with the test data, the results show that the fitted driving cycle can represent the overall traffic condition of electric special-purpose vehicle in Beijing.